Perubahan Fungsi pada Museum Fatahillah Ditinjau dari Teori Poskolonial - Ariani Ariani (Humaniora, 2015)
The Museum of Jakarta Historical, which popularly known as Fatahillah museum, is one of the importance historical buildings in Indonesia with abudance hictorical value. This neoclassic architectural building that was built around the 17th century had already been altered its function for several times, such as: a city hall (stadhius), the house of parliament, a prison especially to hang the convict, a military dorm in the end of colonial period, and a museum in the independence period. All changes of the Fatahillah Museum were observered with qualitative method accompanying with hermeneutics approach to describe its post-colonial study as a relevance result to its casual critical issue and culture. Hence, it could give another perspective of the meaning behind the colonization that ever happened and its impact nowadays. Today, the Fatahillah museum is still standing strong and majestic. The beauty of the architecture becomes a marker that colonial architecture has contributed indirectly to the development of architecture in Indonesia, apart from its function in the past. By studying the interpreted means of the Fatahillah Museum changes in function, the inheritance task is to care for and to preserve the Fatahillah Museum as one of historical witnesses.